ZAKAT PROGRAM APPLICATION FOR CALCULATION USING VISUAL BASIC PROGRAMMING LANGUAGES - Muhamad Kamal Basya; Irwan Bastian, SKom, MMSI (Jurnal Sistem Informasi, 2001)
Computerization on the calculation of Zakat is one of the new breakthrough in theapplication of Islamic teachings and obligations is expected to tithe is not a burden tosociety is but become a habit that can ditumbuh developed so as to create a society ofmutual help and decreases the existing social inequalities.